Efektivitas Media Pembelajaran Geografiku terhadap Hasil Belajar Siswa Pada Materi Pengetahuan Dasar Geografi Kelas X IPS SMAN 1 Bae di Masa Pandemi Covid-19 - Qur’ani, Sunia Bil; Kurniawan, Edi (Edu Geography, 2021)
This study aims to determine the level of effectiveness of my geography learning media in improving student learning outcomes and to find out student learning responses after using my geography learning media on geography basic knowledge material for class X IPS SMAN 1 Bae during the COVID-19 pandemic. Researchers collect data using interviews, observations, questionnaires, tests, and documentation. The data analysis technique used the normality test of pretest and posttest scores, data test, two-average difference test, and gain test. The results showed that the level of effectiveness of using the geography learning media was classified in the medium criteria with the results of N-Gain Percent of 67.93% belonging to the effective criteria. Meanwhile, based on the results of the student response questionnaire, it showed that the students of class X IPS 2 were satisfied with my geography learning media, namely by getting a percentage of 79.8% belonging to the satisfied criteria. The conclusion of this study is that the use of my geography learning media is effective in improving student learning outcomes in the basic knowledge of geography for class X IPS SMAN 1 Bae during the COVID-19 pandemic. Penelitian ini bertujuan untuk mengetahui tingkat efektivitas media pembelajarangeografiku dalam meningkatkan hasil belajar siswa dan mengetahui respon belajar siswa setelah menggunakan media pembelajaran geografiku pada materi pengetahuan dasar geografi kelas X IPS SMAN 1 Bae di masa pandemi COVID-19. Peneliti mengumpulkandata dengan menggunakan wawancara, observasi, angket, tes, dan dokumentasi. Teknik analisis data menggunakan uji nomalitas nilai pretest dan posttest, uji data, uji beda dua rata rata, dan uji gain. Hasil penelitian menunjukkan tingkat efektivitas penggunaanmedia pembelajaran geogrfiku tersebut tergolong pada kriteria sedang dengan hasil NGain Percent sebesar 67,93% yang tergolong pada kriteria efektif. Sedangkan berdasarkan hasil angket respon siswa, menunjukkan bahwa siswa kelas X IPS 2 merasa puas terhadap media pembelaran geografiku yaitu dengan mendapatkan presentase sebesar 80,5% yang tergolong pada kriteria puas. Simpulan dari penelitian ini adalah penggunaan media pembelajaran geografiku efektif dalam meningkatkan hasil belajar siswa pada materi pengetahuan dasar geografi kelas X IPS SMAN 1 Bae di masa pandemi COVID-19